Influence Giving Award to Performance Teacher School Honorary in Raja Ampat Regency - Lengkong , Jeffry Sony Junus; Rawis, Joulanda A.M.; Tambingon, Henny Nikolin; Sauyai, Stanly F M; Dondokambey, Clay J H; Maringka, Riviva W; Paath, Deicy (JR Education, 2024)
This study aims to study the influence of giving awards on the performance of honorary teachers in senior secondary schools (SMA). This study uses a quantitative approach. The research population was all honorary teachers in eight high schools in Raja Ampat Regency, totaling 146 people. 59 people from the total population were selected as samples using simple random sampling techniques with the Taro Yaname and Slovin formula. Data collection uses a questionnaire that has been tested for validity and reliability. The research results show that the performance of honorary teachers is influenced by the awards they receive. Giving awards to honorary teachers has a significant effect on their performance, namely: (1) increased responsibility in carrying out tasks, (2) willingness to work beyond predetermined work standards, (3 ) high enthusiasm and effort to complete tasks well, and (4) willingness and the ability to carry out administrative and teaching tasks.